2010
DOI: 10.1007/s10147-010-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

A case of long-term recurrence-free poorly differentiated neuroendocrine carcinoma of lymph nodes treated by surgical resection without any chemotherapy

Abstract: A 77-year-old man presented with a 2-month history of an enlarged right inguinal lymph node. Diagnostic excisional biopsy of the inguinal lymph node proved it to be a poorly differentiated neuroendocrine carcinoma by histological and immunohistological analyses. We diagnosed a poorly differentiated neuroendocrine carcinoma by histological examination and immunohistological analysis of the resected inguinal lymph node. We performed computed tomographic examination and positron emission tomography, which identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although five other CUP cases were reported to have survived after surgical treatment alone in Japan (18)(19)(20)(21)(22) (Table 4), to our knowledge, this is the first report of a successfully treated case of MSI-H CUP. Of the six cancer cases of unknown primary reported in Japan (including our case) with a long-term survival after surgery alone, four involved intra-abdominal lymph nodes.…”
Section: Discussionmentioning
confidence: 81%
“…Although five other CUP cases were reported to have survived after surgical treatment alone in Japan (18)(19)(20)(21)(22) (Table 4), to our knowledge, this is the first report of a successfully treated case of MSI-H CUP. Of the six cancer cases of unknown primary reported in Japan (including our case) with a long-term survival after surgery alone, four involved intra-abdominal lymph nodes.…”
Section: Discussionmentioning
confidence: 81%
“…There are two models of tumor progression for these nodal neuroendocrine carcinomas from an unknown primary site [5,6]: nodal neuroendocrine carcinoma originates from the LN via formation of malignant precursor cells; and it originates from a spontaneously regressed primary lesion. According to a study reported by Kuwabara et al [7], primary nodal neuroendocrine carcinoma follows a less aggressive course than its metastatic nodal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of previous case reports have also described treatment of PDNEC of unknown primary origin by surgical resection. Hisamori et al [6] reported two cases of PDNEC of unknown primary origin in an inguinal and a pancreaticoduodenal LN, respectively, which were treated by surgical resection alone [8]. Considering the fact that both patients achieved long-term disease-free survival with LN dissection only, their cases probably could have originated from the affected LN itself.…”
Section: Discussionmentioning
confidence: 99%